Perilaku Pemilih Gen Z Pada Pemilihan Presiden Tahun 2024: (Studi Kasus Organisasi Gerakan Pramuka Mahasiswa UNIMED) - Putri Widia Ningsih; Ruth Yessika Siahaan; Dewi Romantika Tinambunan; Ture Ayu Situmeang; Jahya Adiputra Simbolon; Dules Ery Pratama Harahap; Murniwati Lase (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The 2024 Presidential Election in Indonesia is an important moment in political history, with significant involvement from Generation Z (Gen Z). This research aims to analyze the characteristics of Gen Z voting behavior in the Medan State University Student Scout Movement (UNIMED) organization and evaluate the influence of Scout organizational activities on political behavior and decisions to elect Gen Z members at UNIMED. Using qualitative descriptive methods, data was collected through interviews and references from various journals and websites. The research results show that fast access to information via social media influences Gen Z's political views. In addition, Scout activities that focus on character and leadership development also contribute to their political behavior. It is hoped that these findings will enrich academic literature regarding voter behavior, especially Gen Z in Indonesia, as well as provide insight for political parties, presidential candidates and political observers in formulating more effective strategies to attract support from young voters. This research also provides a deeper understanding of the importance of political education and active involvement in the election process for the younger generation.